Analisis semiotika terhadap representasi sikap percaya diri dalam film “Imperfect” karya Ernest Prakasa - Mutia, Farah (Maliki Interdisciplinary Journal, 2024)
Knowing how self-confidence is represented in the film Impercfet by Ernest Prakasa which was broadcast in 2019 will be the aim of the research and this research uses a semiotic approach. Viewing the Imperfect Film and taking notes is a data analysis technique in this research. Many social issues are addressed in the film "Imperfect", especially those related to body image and self-confidence. This research investigates the signs and symbols used in films to explain the meaning associated with self-confidence. Using Roland Barthes' semiotic theory, this research explores these meanings. This research looks at film elements such as characters, settings, costumes, dialogue and storyline. The results show that this film uses many visual and narrative codes to contrast self-distrust and self-acceptance. The visual changes and social interactions experienced by the main character from self-doubt to self-acceptance and self-confidence are depicted. This research found that the film "Imperfect" provides social criticism of women's beauty standards in modern times and a message about the importance of building self-confidence and accepting oneself.